Internetworking with TCP/IP - 390208 Comer, Douglas E.; Stevens, David L. (Englewood Cliffs, NJ : Prentice Hall, 1991)
V.1. Principles, protocols and architecture -- v.2. Design, implementation and internals -- v.3. Client/server programming and applications